PERAN BUDGETING DALAM EFEKTIVITAS MANAJEMEN KEUANGAN: KAJIAN LITERATUR KONSEPTUAL DAN PRAKTIS - Sabila Qurrota A'yun; Nadia Putri Kamila; Muhammad Sodiqul Fikri; Romlah Romlah; Heni Noviarita (STKIP Pesisir Selatan, 2026)
This study aims to analyze the strategic role of budgeting in enhancing the effectiveness of financial management through a conceptual and practical literature review. Budgeting serves as a crucial instrument functioning as a tool for planning, controlling, and evaluating organizational performance amid global economic volatility. The research method employed is a descriptive qualitative literature study by synthesizing relevant sources from Sinta and Scopus databases within the last five years. The findings indicate that the implementation of Performance-Based Budgeting and the integration of digital technology significantly improve resource allocation efficiency by up to thirty percent compared to traditional methods. Active managerial participation in the budgeting process has been proven to substantially reduce the risk of budgetary slack and enhance financial accountability. Furthermore, the digitalization of budgeting processes enables real-time cash flow monitoring, providing adaptive advantages for organizations in responding to rapid market changes. This study emphasizes that the effectiveness of financial management is highly dependent on budget discipline and the transformation of systems from manual to digital approaches. The article contributes theoretically to the development of financial management knowledge and offers practical guidance for managers in optimizing financial performance through more measurable, transparent, and sustainable budgeting policies.